Quality Characteristics and Inhibitory Xanthine Oxidase Potential of 21 Sour Cherry (Prunus Cerasus L.) Varieties Cultivated in China - Wang, Rui; Zhang, Fang; Zan, Shengyue; Gao, Chang; Tian, Changping; Meng, Xianghong (Frontiers in Nutrition, 2021)
This study aims to analyze the physicochemical characteristics and activities of 21 sour cherry cultivars in China. The evaluated accessions differ in several quality traits including weight, moisture, color, total soluble solids, and total acids. Glucose and malic acid were the predominant individual sugar and organic acid in all accessions. The K and Fe were of the highest contents in Érid jubileum (453.887 mg/100g FW) and Meili (2.988 mg/100g FW), respectively. The contents of total phenolics (TP) were from 9.309 to 24.118 mg GAE/g DW, and total flavonoids (TF) were 8.935-27.198 mg RE/g DW, which were significantly highly positively correlated (r= 0.892, p<0.001). M-15, Érdi fubileum, and Érid jubileum showed the highest inhibitory effects on xanthine oxidase, and the IC50 inhibitory were 2.619, 3.117, and 3.940 mg/mL, respectively. This work evaluated the quality and nutritional characteristics of 21 sour cherry cultivars grown in China and explored their potential as an innovative food ingredient for hyperuricemia by evaluating the inhibitory effects of XO. And hese results provide valuable data and new ideas for the future sour cherry breeding program as well as a processing guide.